All-inclusive descriptions of new freshwater snail taxa of the hyperdiverse family Tateidae (Gastropoda, Caenogastropoda) from the South Island of New Zealand - Verhaegen, Gerlien; Haase, Martin (European Journal of Taxonomy, 2021)
Four new species and one new subspecies of tateid freshwater gastropods are described from the north of the South Island of New Zealand, Catapyrgus jami sp. nov., Opacuincola lisannea sp. nov., O. gretathunbergae sp. nov., O. mete kahurangi ssp. nov. and Obtusopyrgus farri sp. nov. The species are integratively defined based on a combination of shell morphological, anatomical and mitochondrial DNA data. Morphological and anatomical data were generated by morphometrics, scanning electron microscopy, as well as micro-computed tomography. The genetic data were basis of phylogenetic analyses and incorporated into the diagnoses. The new taxa occur in springs or spring-like habitats, i.e., shallow, slow-flowing sections of small streams except for O. mete kahurangi subsp. nov., which was collected from rough rocks in a river, where the snails sat in small depressions. None of the species exceeded 2.75 mm in length. Opacuincola gretathunbergae sp. nov. and Obtusopyrgus farri sp. nov. are pigmented and true crenobionts, while C. jami sp. nov. and the sympatric Opacuincola lisannea sp. nov. have eyes of reduced size and lack epidermal pigment, hence, probably dwell in the transitional zone of epigean and groundwaters.